Impacto da gamificação no processo de ensino e aprendizagem da disciplina de desenvolvimento e gestão de projetos - Nery, William Denner Roberto (Brasil, 2023)
This article aims to analyze the impact of gamification on teaching project development and management. The conceptual approaches adopted were based on behavioral and cognitive theories, exploring how gamification can positively influence these aspects. The methodological procedures involved the implementation of gamified activities, data collection through questionnaires, and descriptive statistical analysis of the results. The originality of this study lies in investigating the impact of gamification in a specific educational context and analyzing its consequences for student learning. The results highlight the importance of gamification as an effective pedagogical strategy, providing a more engaging and motivating learning experience. Additionally, they contribute to the understanding of gamification in the field of education and offer insights for educators who wish to incorporate gamified elements into their teaching environments, aiming to promote more efficient and appealing learning. The obtained results also revealed that gamification had a significant impact on the participants' interest and engagement, as well as on their performance and skill development in the discipline. Furthermore, gamification was able to satisfy students' basic psychological needs, such as autonomy, competence, and social relatedness.